A imunidade tributária do ITBI quando da integralização de bem imóvel a pessoa jurídica como capital subscrito - Malta, Clarissa Pitanga (2022)
The present work seeks to analyze the scope of the tax immunity of the on Transfer of immovable property, in the specific case of art. 156, §2, item I, of the Federal Constitution, through which it establishes tax immunity in payment of immovable property in the realization of capital. The study also uses the judgment in Extraordinary Appeal No. 796,376 by the Federal Supreme Court and demonstrates the importance of legal interpretations from the dictates constitutional. The method used to obtain the results was a survey doctrinal and jurisprudential. In conclusion, therefore, that the questions presented show that the Municipal Tax Authorities from interpretations distortions of Theme 796, of general repercussion, are charging on the properties paid in to the subscribed capital of the legal entity the Tax on Transfer of Real Estate in relation to the difference in the registered value of the property and its market value